1992
DOI: 10.1038/355457a0
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional hierarchy involved in mammalian cell-type specification

Abstract: Although transcriptional hierarchies have been extensively studied in invertebrates, their involvement in mammalian cell-type specification is poorly understood. Here we report a hepatocyte transcriptional cascade suggested by the expression patterns of hepatic transcription factors in dedifferentiated hepatomas and hepatocyte: fibroblast hybrids in which the liver phenotype was extinguished. These results indicated that the homeoprotein hepatocyte nuclear factor-1 alpha (HNF-1 alpha), and HNF-4, a member of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
309
3
9

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(343 citation statements)
references
References 27 publications
22
309
3
9
Order By: Relevance
“…5B). This suggested that HNF-4␣ could directly activate HNF-1␣ gene transcription as reported in hepatocytes (26,36). The expression of several genes linked to differentiation and metabolism and identified to be upregulated during the coculture kinetics ( Fig.…”
Section: Hnf-1␣ Is a Downstream Target Of Hnf-4␣ In Iec And Cooperatesupporting
confidence: 62%
See 1 more Smart Citation
“…5B). This suggested that HNF-4␣ could directly activate HNF-1␣ gene transcription as reported in hepatocytes (26,36). The expression of several genes linked to differentiation and metabolism and identified to be upregulated during the coculture kinetics ( Fig.…”
Section: Hnf-1␣ Is a Downstream Target Of Hnf-4␣ In Iec And Cooperatesupporting
confidence: 62%
“…In addition, HNF-4␣ is able to rapidly induce HNF-1␣ gene transcript and protein levels within the IEC context. This molecular interaction is probably due to a direct transcriptional action of HNF-4␣ on the HNF-1␣ promoter since it was previously reported that HNF-4␣ can directly control the transcription of HNF-1␣ in hepatocytes (26,36). HNF-1␣ was also shown to control HNF-4␣ transcription specifically in pancreatic cells (3), a relationship that was not observed in our culture model system.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, the PEPCK, L pyruvate kinase and aldolase B promoters, which contain a functional HNF-1 site, also bind HNF-3 or HNF-4. Since HNF-3 and HNF-4 stimulate transcription of the HNF-la gene [153], and therefore occupy a higher position in the hierarchy of transcription factors, one could have expected that they need not bind to genes regulated by HNF-1. The fact that they do suggests a functional redundancy or a requirement in vivo for a co-operation between liver-specific factors to promote protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in hepatoma cell lines and hepatocytederived hybridomas, loss of C/EBP␣ does not extinguish the hepatocyte phenotype (49,50). Thus, although C/EBP␣ has a clear antiproliferative effect in adipocytes, its role in the liver appears more complex.…”
Section: Figmentioning
confidence: 99%